Laparoscopic Versus Open Resection Following Stent-Bridge to Surgery for Obstructive Colorectal Cancer: A Systematic Review and Meta-Analysis of Perioperative Outcomes - Aflis; Made Mulyawan; Made Agus Dwianthara Sueta (HM Publisher, 2026)
Background: Obstructive colorectal cancer (OCRC) constitutes a surgical emergency historically managed by immediate open resection, a procedure fraught with elevated morbidity and mortality rates due to the physiological derangement of the patient. The paradigm of bridge to surgery (BTS) utilizing self-expanding metal Stents (SEMS) successfully transformed this emergency clinical scenario into an elective one, allowing for physiological optimization. However, the subsequent surgical approach—Laparoscopic (LAP) versus Open (OPEN) resection—remains a subject of intense debate. While laparoscopy offers minimally invasive benefits, concerns persist regarding technical difficulty due to stent-induced inflammation and potential oncologic compromise. Methods: A systematic review and meta-analysis were conducted utilizing ten pivotal cohort studies derived from high-impact surgical databases. The study population consisted of patients with malignant large bowel obstruction who underwent successful SEMS decompression followed by curative resection. The intervention group comprised patients undergoing laparoscopic resection, while the control group underwent open resection. Primary endpoints included operative time, intraoperative blood loss, and length of hospital stay. Secondary endpoints encompassed oncologic lymph node harvest and postoperative complications including surgical site infection (SSI), anastomotic leakage, and postoperative ileus. Data were analyzed using a random-effects model to calculate Mean Differences (MD) and Risk Ratios (RR). Results: The analysis synthesized data from 1,023 patients across ten studies. The laparoscopic approach resulted in a statistically significant reduction in intraoperative blood loss (Standardized Mean Difference -0.84; p < 0.001) and a shorter length of hospital stay (Mean Difference -3.12 days; p < 0.001). Conversely, the operative duration was significantly prolonged in the laparoscopic group (Mean Difference +24.50 minutes; p = 0.002). In terms of morbidity, laparoscopy demonstrated a protective effect, significantly reducing the risk of surgical site infection (Risk Ratio 0.42; p = 0.003) and postoperative ileus (Risk Ratio 0.58; p = 0.04). Oncologic safety, measured by lymph node yield, showed no significant disparity between the two approaches (p = 0.76). Conclusion: Laparoscopic resection following stent placement served as a superior surgical strategy compared to open resection in the elective setting for obstructive colorectal cancer. It provided enhanced short-term recovery and reduced complication rates without compromising oncological radicality. The observed increase in operative time reflected the technical complexity of the post-stent anatomy but did not negate the perioperative benefits.